2021
DOI: 10.3390/ijerph18137117
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Stress-Buffering Effects of COVID-19-Related Changes in Exercise Activity on the Well-Being of German Sport Students

Abstract: Maintaining or initiating exercise activity in the COVID-19 pandemic may act as a buffer against the observed stress-related deterioration in well-being, with emotion regulation (ER) discussed as a possible moderator. Therefore, the present study investigated the interaction between stress, exercise activity (EA), and ER on mood. In an online survey, 366 German sports science students (56% women, Mage = 23.04, SD = 2.87) reported their stress levels (general and COVID-19-specific), mood (energy, valence, calmn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 108 publications
(195 reference statements)
0
3
0
Order By: Relevance
“…Numerous studies have shown that due to the COVID-19 confinement an inverse association has been observed between reduced physical activity and well-being in the general population [41,42], and especially with negative consequences for mental health, as the symptoms of stress and depression increase due to a lack of physical activity [43][44][45]. Athletes are an especially at-risk group for suffering these negative psychological consequences; reduced physical activity has had a negative effect on their sports performance, and with it increased their stress and negative mood states [46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that due to the COVID-19 confinement an inverse association has been observed between reduced physical activity and well-being in the general population [41,42], and especially with negative consequences for mental health, as the symptoms of stress and depression increase due to a lack of physical activity [43][44][45]. Athletes are an especially at-risk group for suffering these negative psychological consequences; reduced physical activity has had a negative effect on their sports performance, and with it increased their stress and negative mood states [46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…At first, sports participation might be reduced due to lifestyle changes in response to the COVID-19 pandemic ( Buldú et al, 2020 ; DiFiori et al, 2021 ; Drewes et al, 2021 ). Reduced sports activity and participation could induce physical and psychological adverse symptoms, including distress, feeling blue, stress, and depressed mood ( Qi et al, 2020 ; Giessing et al, 2021 ; Sa et al, 2021 ). For the compensation of withdrawn sport participation and overcoming adverse physical and psychological events, the exploration for alternative activities or healing methods could be tried in online contact technology with a variety of content on different platforms using virtual reality and metaverse technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Although a great number mental health support services has already been introduced such as 24-h free psychological counseling hotline and free mental health assistance seminars ( 1 ), we still strongly recommend that mental health care systems and related organizations continue to provide various mental health assistance, as the impact of the quarantine on people may be long-lasting ( 49 , 65 ). As for individuals during the quarantine, maintaining a normal routine and physical activity ( 9 , 11 , 66 ), doing some gardening ( 1 ), and reducing excessive attention to pandemic news ( 47 ) can be particularly helpful in alleviating psychological stress and promoting personal mental well-being.…”
Section: Discussionmentioning
confidence: 99%